Prediction of Equine Abortion with Measurement of Serum Magnesium Level - Kurban, İbrahim and Günay Uçmak, Zeynep and Uçmak, Melih (Acta Scientiae Veterinariae, 2024)
Background: Magnesium (Mg) is the 4th most abundant cation in the mammalian body. Mg activates many enzymes and affects the nerve conduction, uterine contractility and other smooth muscle contractility. Mg is a calcium antagonist. Its effect on uterine smooth muscle is relaxation and tocolysis. Decrease of Mg plays an important role in labor and deficiency of Mg has been associated with various pregnancy complications in women. However, less is known about the reproductive roles of Mg in mares. This study aimed to measure and compare the maternal serum Mg concentration in 2nd trimester abortus and healthy pregnancy in Arabian mares and find the relationship of serum Mg concentration with abortus. Materials, Methods & Results: The study groups consisted of 8 healthy foaling mares (group H) and 8 mares with spontaneous abortion within the 2nd trimester of their pregnancies (group A). In group A, Mg was analyzed in the serum samples belonging to the 1st months of pregnancies and the months in which 2nd trimester abortions occurred (the last collected sample before abortion). In group H, serum samples from the 1st months of pregnancies and samples in the pregnancy months corresponding to the abortion month of each mare in group A were analyzed. In group A, serum Mg concentration decreased from the 1st month to the abortion month (28.12 ± 1.27 µg/g and 24.54 ± 0.69 µg/g, respectively) whereas it increased from the 1st month to the matching gestational month in group H (30.43 ± 0.36 µg/g and 36.16 ± 0.66 µg/g, respectively). A significantly lower serum Mg concentration was observed in abortion month for group A (24.54 ± 0.69 µg/g) versus the matched gestational month for group H (36.16 ± 0.66 µg/g). Discussion: Studies conducted in women have shown an association between low maternal serum Mg concentration and abortion or preterm labor. Significantly lower serum Mg concentrations of women with preterm labor versus their healthy pregnant controls were reported. Consistent with these previous reports in women, in this study a significantly lower serum Mg concentration was observed in abortion month for group A versus the matched gestational month for group H. However, it would not be right to compare serum Mg concentrations of the present study with the human studies mentioned, due to the species difference. Besides, we could not find any report evaluating the serum Mg concentration in mare abortion. Low serum Mg concentrations with preterm labor in women despite their various etiology were reported. In this study the reasons for the abortions in mares were not determined and may be various. Consistent with the previous reports in women, in the present study an association between low serum Mg concentration and abortion was found in Arabian mares (although the probably varied reasons for abortion). Rather than attributing the cause of all cases to Mg deficiency, it is more appropriate to interpret Mg as an element that participates in and reflects the stimulation process of uterine contractility caused by various abortion factors in mares. In conclusion; maternal serum Mg concentration of the abortion month in Arabian mares was significantly lower both compared to the 1st gestational months of these mares and compared to the abortion-matched months of ongoing healthy pregnancies. Further studies considering the results of this pioneering study may lead the use of serum Mg concentration as a predictor of abortion in mares thus to pave the way for applying the necessary preventions during the high-risk pregnancies. Keywords: mare, abortion factors, preterm labor, magnesium, uterine contractility, pregnancy, spectrophotometry.